Farmers’ perceptions and awareness of cattle feedlots as a climate-smart approach to enteric methane emissions - Beautiful Isabel Mpofu; Mhlangabezi Slayi; Leocadia Zhou; Ishmael Festus Jaja (Heliyon)
The perceptions of farmers regarding communal feedlots and their role in reducing enteric methane emissions have received limited attention in research. This study aims to examine farmers’ perceptions, assess awareness, and identify barriers to adopting feedlots as a climate-smart practice to enteric methane emissions in rural communities in the Eastern Cape Province, South Africa. 161 structured, paper-based questionnaires were distributed among smallholder cattle farmers around three feedlot locations. Most farmers had heard about feedlots (67.7 %); however, only a few (19.9 %) participated. The lack of knowledge about feedlot operations was the main factor influencing farmers’ participation in feedlots. Most farmers did not perceive feedlots as a climate-smart approach to reducing enteric methane output (53.8 %), with few sure (9.6 %) and others unsure (36.5 %). When asked about the reasons for their perceptions of feedlots as a climate-smart approach to mitigating methane, many farmers were unsure of the reasons (86.5 %), with the least believing it could be related to poor feed quality (1.9 %). The availability of financial resources and level of education were the key factors influencing farmers’ willingness to adopt feedlots as a climate-smart practice. These findings emphasise the importance of targeted educational workshops and support systems to enhance farmers’ awareness and promote the adoption of cattle feedlots as a climate-smart approach. The findings can also inform policy and practice to address perceived feedlot drawbacks, such as feed provision and technical assistance, and improve their successful implementation. However, further research is needed to explore farmers’ perceptions of cattle feedlots as a climate-smart practice.